Unmanned Aerial System (UAS) and Structure From Motion (SfM) 3-dimensional modeling of intertidal archaeological features in Fulford Harbour, Saltspring Island, British Columbia, Canada. - Laidlaw, Shawn (2017)
Clam garden intertidal features were constructed and maintained by First Nations peoples over thousands of years and are identified throughout coastal British Columbia and Alaska. The thesis study site is the Gulf Islands National Park Reserve Clam Garden Restoration Project, in Fulford Harbour on Salt Spring Island, British Columbia, Canada. Images were gathered of the Fulford Harbour clam garden using a UAS – or drone and these were processed using SfM software to create a DSM and Orthomosaic of the clam garden. This approach was compared with existing technologies such as LiDAR and traditional photogrammetry, and further applications in the intertidal environment and archaeological fields were considered. Novel techniques were developed, such as the use of natural features as GCPs. It was demonstrated that developing a DSM and orthomosaic is possible for scientific purposes by non-experts in geospatial and survey techniques, and that this can be executed with high resource efficiency.